Clinical nutrition case studies - Billon, Wayne (Brooks Cole, 2006)
CLINICAL NUTRITION CASE STUDIES includes over 40 clinical cases, introducing students to the the broad range of clinical situations faced as a diet therapist, from alcoholic cirrhosis and insulin- and noninsulin-dependant diabetes to vegetarianism, body building, atherosclerosis, and much more. Each case includes a detailed description of patients' histories and nutritional problems, followed by a list of questions that invite students to apply their classroom and clinical lessons to the situations presented.